1973
DOI: 10.1111/j.1752-1688.1973.tb05851.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF SELECTED HERBICIDES ON BACTERIAL POPULATIONS IN AN AQUATIC ENVIRONMENT1

Abstract: Heterotrophic, mesophilic bacteria derived from, and maintained in, a freshwater environment were subjected to three classes of herbicides. Diuron, 2,4,5-Trichlorophenoxyacetic acid, and paraquat, used as water soluble solutions, were added (0.7 and Paper No. 73090 of the Water Resources BuZZerin. Discussions are open until July 1, 1974.'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Bacteria which may serve as pollution indices may enter water with the pollutant, and thereby be adapted to the chemical substrate provided in the pollutant, or they may be naturally occurring aquatic bacterial species which can adapt to the chemical nature of a pollutant. In the diluted medium of polluted water they may grow more rapidly and aid in the degradation of organic molecules or the cycling of simpler chemicals into aquatic food webs (Ferebee and Guthrie, 1973;Patrick and Loutit, 1976 Before such bacterial indicators and their activities can be properly evaluated it is necessary to'understand more of the responses of natural aquatic bacterial populations to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria which may serve as pollution indices may enter water with the pollutant, and thereby be adapted to the chemical substrate provided in the pollutant, or they may be naturally occurring aquatic bacterial species which can adapt to the chemical nature of a pollutant. In the diluted medium of polluted water they may grow more rapidly and aid in the degradation of organic molecules or the cycling of simpler chemicals into aquatic food webs (Ferebee and Guthrie, 1973;Patrick and Loutit, 1976 Before such bacterial indicators and their activities can be properly evaluated it is necessary to'understand more of the responses of natural aquatic bacterial populations to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Factors which affect the adaptation and growth of heterotrophic bacterial populations in aquatic systems include water temperature, available nitrate and phosphate sources, and the nature and concentration of organic substrate present Ferebee and Guthrie, 1973;Ferguson, etal., 1976;Hobbie, 1971). Cherry, et al, (1974;1977) have reported that bacterial populations in coal ash basin effluent maintained year round stability with greatest changes in diversity and numbers coming after large changes in ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Direct toxicity of herbicides to most aquatic organisms has not been shown. Ferebee (1972), however, demonstrated that 2,4,5-T, paraquat and diuron had different effects on the aerobic, heterotrophic bacterial populations of one reservoir. He concluded that 2,4,5-T had little effect on the total number of bacteria present, while paraquat application resulted in a net population increase and diuron in a net decrease.…”
mentioning
confidence: 89%
“…Investigators do not completely agree on the fate of herbicides in an aquatic environment; however, Funderburk and Bozorth (1967) have reported that many herbicide formulations persist for long periods in water and resist bio-degradation. Ferebee (1972) reported that 2,4,5-T, paraquat and diruon all persisted in a studied aquatic system for at least a 45-day test period.…”
mentioning
confidence: 92%
“…Microcosms used for testing herbicides have usually contained water, plants and sediment (Frank et al, 1961 ;Hodgson & Otto, 1963) but have varied in size from 500 ml (Robson et al, 1976) to over 50 1 (Ferebee & Guthrie, 1973;Simsiman et al, 1972). Such microcosms, although intrinsically variable (Cooke, 1977) are similar in terms of community metabolism (Abbot, 1966) and the succession of changes that occur in them (Cooke, 1967).…”
Section: Introductionmentioning
confidence: 99%